Improved combined mutation clonal selection algorithm - Paw J.K.S.; Hen C.K.; Yan K.W.; Ann Y.S. (2023)
In this paper, the performance of a clonal selection optimization algorithm implementing a combined mutation strategy using Gaussian and Cauchy mutations was further improved with the addition of two new operators, namely the Cell Repair Operator (CPO) and Dynamic Mutation Size Operator (DMSO). The new and improved algorithm was tested using various unimodal and multimodal test functions to illustrate the improvements of the algorithm. The test results indicate that the added operators have significantly improved the performance of the algorithm in terms of accuracy and performance. 2012 IEEE.